Contemporary Components Connected to the Evolution of Football - Lucian Constantin Panescu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
Romanian football is deeply ingrained in the national culture and is heavily impacted by public life. It is also generally recognized as a social phenomena in many different contexts. Moreover, the sector has historically been linked to certain political and ideological stances, which add to the extremely antagonistic environment. The purpose of this research is to conduct a longitudinal study of Romania's own coefficients and examine the statistical findings about the evolution of domestic clubs in Europe in relation to past performances, rather than comparing Romania's coefficients with those of other nations. The results indicate that integrating stakeholders and developing new ties can increase industry trust.